The 1866 Prussian Occupation of Prague in the Light of Documents from the City Archives (Theatrum historiae, 2023)
While the international political and military issues of the Austro-Prussian War and the effects of the Prussian invasion on selected regions of the Czech lands in 1866 enjoy consistent attention from historiography, contemporary life in Prague – occupied at the time without a fight – paradoxically ranks among the less explored subjects. The following study deals with the events of the summer months of this year, focusing on the key role of the local city government led by the burgomaster Václav Bělský. The author recaps existing works on the topic and presents relevant documents preserved for this period in the Prague City Archives: minutes from council meetings, the agenda of the praesidium, accounting materials, charters, manuscripts, narrative sources, documents of artistic reception, and others. Through the optics of these sources the author shows how city councillors and representatives undertook to supply the occupying garrison and secure public order, while also recalling their care for refugees, the wounded, the unemployed, and starving people. This includes the essential fact that maintaining the viability of the Bohemian capital and preventing fatal losses was successful despite the absence of provincial armed forces, as well as the state authorities and the majority of the assembly, which had been evacuated from Prague in advance.
Keywords: Austro-Prussian War of 1866; occupation; Prague; Václav Bělský; Prague City Archives